The Implementation of Rehabilitation for Drug Using Police Members (Case Study in the Blora Police Legal Area) - Indah Purnama Dewi; Asri Agustiwi; Bintara Sura Priambada (LEGAL BRIEF, 2022)
In general, the Indonesian people and the international community are today confronted with a very concerning scenario as a result of the widespread unlawful usage of numerous sorts of narcotics. Narcotics misuse is employed not just by the general populace, but also by the police. As we all know, the police have a critical role in combating and eliminating drug usage in society. The legal system that applies in Indonesia as a state of law certainly upholds equality before the law and the government for every citizen, not to mention perpetrators of criminal acts committed by law enforcement officers themselves, in this case members of the Indonesian police, who must go through a legal process in accordance with the applicable legal rules if proven legally and convincingly to commit a crime. The investigation of police officers is governed by the rules of the general criminal procedure legislation and Law Number 2 of 2002 regulating the Indonesian National Police. Thus, it is expected that the vision and mission of determining criminal sanctions can be realized, namely creating a deterrent effect for all those who have violated the rules of criminal acts regardless of the person who committed the crime, and this is expected to be a means of enforcing criminal law by the police. The issue at hand is the introduction of rehabilitation programs for active members of the National Police (Case Study in the Legal Area of the Blora Resort Police). This study employs normative legal research. The normative research approach is strongly tied to library research because it will require secondary data from the library